Institutions, trade, and integration: what can be expected within the enlarged EU? - Michaela Fuchs; Klaus Wohlrabe (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2008)
This paper investigates the potential for a further increase in trade between the fifteen old EU members and the twelve new countries having joined in 2004 and 2007 that results from a convergence of the new members' institutions towards the level of the EU-15 in accordance with the Acquis Communautaire. To this aim we estimate a gravity model applying both static and dynamic panel data techniques and incorporate detailed variables measuring institutional quality. We conclude that there is further potential for trade resulting from the successive convergence of the new members institutional framework towards EU standards.
Keywords: C23; F10; F15; O17; P30; 330; European integration; institutions; gravity model; trade potential